Synthesis, Structural Properties and Antibacterial Activity of Vorinostat Loaded on Carbon Nanotubes or Iron Oxide Nanoparticles - Abed, Dhulfiqar; Habeeb, Saba Abdulmunem; Al-Jibouri, Lena Fadhil; Hammadi, Asmaa Hashim; Kbah, Noor Zuhair (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: In this work, Carbon Nanotubes (CNTs) and Iron Oxide Nanoparticles (IONPs) were successfully synthesized and their antibacterial activity were evaluated against Staphylococcus aureus (Gram-positive) and Pseudomonus aeruginosa (Gram-negative). Vorinostat, (SAHA) is a histone deacetylase inhibitor has recently shown the potential as an antibacterial agent through the genewration of Reactive Oxygen Species (ROS). Materials and Methods: Vorinostat (SAHA) was synthesized using conventional chemical reaction and characterized using FTIR, 1H-NMR and 13C-NMR. CNTs were synthesized using flame fragments deposition, and the IONPs were synthesized via co-precipitation method. SAHA was loaded on synthesized IONPs or CNTs, and the nanomaterial were analyzed using SEM, XRD, and FTIR. The antimicrobial activity of SAHA loaded IONPs or CNTs against gram positive and gram negative bacteria was quantitatively evaluated using agar well diffusion method. Results: SAHA was successfully characterized susing FTIR, 1H-NMR and 13C-NMR. Data from XRD analysis reveal appropriate loading of SAHA into the nanoparticles. The XRD analysis for the crystallite sizes of SAHA/ Fe2O3 and Fe2O3 nanoparticles were 54.2 and 38.4 nm, respectively. FTIR data indicated SAHA surface-bounding over the IONPs and CNTs in addition to SAHA encapsulation. No activity was observed against Pseudomonas aeruginosa, and a concentration dependent increase in the activity against Staphylococcus aureus. SAHA demonstrated a modest 120 mm inhibition zone against S. aureus. The inhibition zone increase considerably to 30-mm when 20 mg/mL of IONPs were used. Likewise, a 28 mm inhibition zone was produced with SAHA loaded CNTs. Conclusion: These results show that SAHA loaded nanostructures significantly increase their antibacterial activity against gram positive bacteria as a result of better drug delivery, membrane penetration, and increased oxidative stress. These results revealed the potential agonistic antibacterial activity of SAHA-loaded nanostructures, which could be associated with better drug delivery, membrane permeability, and increased oxidative stress in bacterial cell.
Keywords: SAHA; Carbon Nanotube (CNTs); Iron Oxide Nanoparticles; Antibacterial Activity; Drug Delivery